ATX-3, CDC-48 and UBXN-5: a new trimolecular complex in Caenorhabditis elegans - Rodrigues, Ana João (2009)
Ataxin-3 is the protein involved in Machado-Joseph disease, a neurodegenerative disorder caused by a polyglutamine expansion. Ataxin-3 binds ubiquitylated proteins and acts as a deubiquitylating enzyme in vitro. It was previously proposed that ataxin-3, along with the VCP/p97 protein, escorts ubiquitylated substrates for proteasomal degradation, although other players of this escort complex were not identified yet. In this work, we show that the Caenorhabditis elegans ataxin-3 protein (ATX-3) interacts with both VCP/p97 worm homologs, CDC-48.1 and CDC-48.2 and we map the interaction domains. We describe a motility defect in both ATX-3 and CDC-48.1 mutants and, in addition, we identify a new protein interactor, UBXN-5, potentially an adaptor of the CDC-48-ATX-3 escort complex. CDC-48 binds to both ATX-3 and UBXN-5 in a non-competitive manner, suggesting the formation of a trimolecular complex. Both CDC-48 and ATX-3, but not UBXN-5, were able to bind K-48 polyubiquitin chains, the standard signal for proteasomal degradation. Additionally, we describe several common interactors of ATX-3 and UBXN-5, some of which can be in vivo targets of this complex.